Feasibility of Permanent Stenting with Solitaire FR as a Rescue Treatment for the Reperfusion of Acute Intracranial Artery Occlusion - Woo, H.G. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: The Solitaire FR can be used not only as a tool for mechanical thrombectomy but also as a detachable permanent stent. Our aim was to assess the feasibility and safety of permanent stent placement with the Solitaire FR compared with other self-expanding stents for intracranial artery recanalization for acute ischemic stroke. MATERIALS AND METHODS: From January 2011 through January 2016, we retrospectively selected 2979 patients with acute ischemic stroke. Among them, 27 patients who underwent permanent stent placement (13 patients with the Solitaire FR [Solitaire group] and 14 patients with other self-expanding stents [other stent group]) were enrolled. The postprocedural modified TICI grade and angiographic and clinical outcomes were assessed. The safety and efficacy of permanent stent placement of the Solitaire FR for acute large-artery occlusion were evaluated. RESULTS: Stent placement was successful in all cases. Modified TICI 2b–3 reperfusion was noted in 84.6% of the Solitaire group and in 78.6% of the other stent group. Procedural time was significantly shorter in the Solitaire group than in the other stent group (P = .022). Shorter procedural time was correlated with favorable outcome (ρ = 0.46, P = .035). No significant differences were found in the modified TICI grade, NIHSS score, mRS, and hemorrhagic transformation rate between the 2 groups. The acute in-stent thrombosis rate at discharge was significantly lower when a glycoprotein IIb/IIIa inhibitor was injected during the procedure (P = .013). CONCLUSIONS: Permanent stent placement with the Solitaire FR compared with other self-expanding stents appears to be feasible and safe as a rescue tool for refractory intra-arterial therapy.